2021
DOI: 10.1155/2021/5212721
|View full text |Cite|
|
Sign up to set email alerts
|

Yap-Hippo Signaling Activates Mitochondrial Protection and Sustains Breast Cancer Viability under Hypoxic Stress

Abstract: Yes-associated protein (Yap) is a transcriptional regulator that upregulates oncogenes and downregulates tumor repressor genes. In this study, we analyzed protein expression, RNA transcription, and signaling pathways to determine the function and mechanism of Yap in breast cancer survival during hypoxic stress. Yap transcription was drastically upregulated by hypoxia in a time-dependent manner. siRNA-mediated Yap knockdown attenuated breast cancer viability and impaired cell proliferation under hypoxic conditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 69 publications
(76 reference statements)
0
6
0
Order By: Relevance
“…To prevent apoptosis, the cell deactivates Hippo signaling to activate the transcriptional coactivator Yap to upregulate Hippo gene targets including SLC2A1, which encodes glucose transporter GLUT1. The upregulation of GLUT1 promotes glucose metabolism, which subsequently promotes the upregulation of BCL-xL (26,(29)(30)(31). Previous studies demonstrate that a reduction in GLUT1 protein expression increases Bax, Bak, Bim and Bid (pro-apoptotic) and inhibits MCL-1 and BCL-xL (36).…”
Section: Cellular Apoptosis Plays An Important Role As An Innate Defe...mentioning
confidence: 99%
See 1 more Smart Citation
“…To prevent apoptosis, the cell deactivates Hippo signaling to activate the transcriptional coactivator Yap to upregulate Hippo gene targets including SLC2A1, which encodes glucose transporter GLUT1. The upregulation of GLUT1 promotes glucose metabolism, which subsequently promotes the upregulation of BCL-xL (26,(29)(30)(31). Previous studies demonstrate that a reduction in GLUT1 protein expression increases Bax, Bak, Bim and Bid (pro-apoptotic) and inhibits MCL-1 and BCL-xL (36).…”
Section: Cellular Apoptosis Plays An Important Role As An Innate Defe...mentioning
confidence: 99%
“…The Hippo pathway regulates various innate and metabolic responses including glycolysis and apoptosis (27)(28)(29). When Hippo signaling is deactivated, activated Yap binds TEAD and induces SLC2A1 [encodes glucose transporter 1 (GLUT1)] upregulation, thereby promoting glycolysis and cell growth and apoptosis inhibition (26,(29)(30)(31). GLUT1 is a highly conserved glucose transporter that regulates glucose metabolism and prevents apoptosis by regulating the BCL-2 family of proteins.…”
mentioning
confidence: 99%
“…Interestingly, this inhibits another responsible protein (Yes-associated protein or YAP) 16 . The role of YAP is to maintain the mitochondria 127 . As such, stimulation of ARF results in lesser YAP, resulting in an apoptosis cascade via the mitochondrial pathway.…”
Section: Selective Interaction Of Carbon Dots With Cancer Cellsmentioning
confidence: 99%
“…The ARF protein can inhibit yes-associated protein (YAP) in the nucleus, inhibiting prostate cancer cell lines. Thus, in such a situation, CDs enhanced ARF's ability to inhibit YAP protein crucial in maintaining the viability [127] of tumor cells. While the actual occurrence of cell death inducement is still a mystery, the above data provides insight into the interaction and mechanism of cell apoptosis due to CDs exposure.…”
Section: Selective Interaction Of Carbon Dots With Cancer Cellsmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%